1974
DOI: 10.1021/ba-1974-0131.ch010
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Bituminous Coal Char Gasification with Gases Containing Steam and Hydrogen

Abstract: Quantitative correlations developed to describe coal char gasification kinetics are consistent with experimental data obtained under a wide range of conditions with both differential and integral contacting systems. The correlations are developed using data obtained at constant environmental conditions with a thermobalance apparatus and a differential fluid bed system at 1500°-2000°F and 1-70 atm with a variety of gases and gas mixtures. The correlations are based on an idealized model of the gasification proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0
2

Year Published

1976
1976
2002
2002

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(14 citation statements)
references
References 13 publications
0
12
0
2
Order By: Relevance
“…More complex models capable of fitting a wider range of experimental data have been proposed by Zahradnik and Glenn (1971) and Johnson (1974), but the above theory satisfies our present needs. The reactions described above, along with the appropriate rate expressions, comprise our kinetic model.…”
Section: K1-rtmentioning
confidence: 79%
“…More complex models capable of fitting a wider range of experimental data have been proposed by Zahradnik and Glenn (1971) and Johnson (1974), but the above theory satisfies our present needs. The reactions described above, along with the appropriate rate expressions, comprise our kinetic model.…”
Section: K1-rtmentioning
confidence: 79%
“…At this time no clear-cut definition exists as to where slow decomposition ends and rapid decomposition begins, although Johnson (1974) reported that slow decomposition may persist with heating rates as high a·s 6000°C/min.…”
Section: 11 Coal Devolatilization·mentioning
confidence: 99%
“…Although many papers related to coal reactivity have been published, few describe detailed studies on the kinetics. [11][12][13] However, some authors have recently reported kinetic studies on the gasification process, using CO 2 , H 2 , steam, and a mixture of steam and hydrogen as gasification agents. 14,15 The uncatalyzed carbon-hydrogen reaction has been extensively studied, and several postulated mechanisms and rate expressions have been presented.…”
Section: Introductionmentioning
confidence: 99%